Comparative toxicity and liver transcriptomics of legacy and emerging brominated flame retardants following 5-day exposure in the rat. (10th October 2020) - Shockley, Keith R.; Cora, Michelle C.; Malarkey, David E.; Jackson-Humbles, Daven; Vallant, Molly; Collins, Brad J.; Mutlu, Esra; Robinson, Veronica G.; Waidyanatha, Surayma; Zmarowski, Amy; Machesky, Nicholas; Richey, Jamie; et al.
Graphical abstract: Highlights: Toxicity of legacy and emerging brominated flame retardants. 5-Day Toxicogenomic studies. Liver toxicity. Benchmark dose analysis using toxicogenomic data. Abstract: The relative toxicity of three legacy and six emerging brominated flame retardants* was studied in the male Harlan Sprague Dawley rat. The hepatocellular and thyroid toxicity of each flame retardant was evaluated following five-day exposure to each of the nine flame retardants (oral gavage in corn oil) at 0.1–1000 μmol/kg body weight per day. Histopathology and transcriptomic analysis were performed on the left liver lobe. Centrilobular hypertrophy of hepatocytes and increases in liver weight were seen following exposure to two legacy (PBDE-47, HBCD) and to one emerging flame retardant (HCDBCO). Total thyroxine (TT4) concentrations were reduced to the greatest extent after PBDE-47 exposure. The PBDE-47, decaBDE, and HBCD liver transcriptomes were characterized by upregulation of liver disease-related and/or metabolic transcripts. Fewer liver disease or metabolic transcript changes were detected for the other flame retardants studied (TBB, TBPH, TBBPA-DBPE, BTBPE, DBDPE, or HCDBCO). PBDE-47 exhibited the most disruption of hepatocellular toxic endpoints, with the Nrf2 antioxidant pathway transcripts upregulated to the greatest extent, although some activation of this pathway also occurred after decaBDE, HBCD, TBB, and HCBCO exposure. These studies provide information that can be used for prioritizing the need for more in-depth brominated flame retardant toxicity studies.